The effectiveness of destruction vestibular receptors and its mechanisms in treating amnestic syndrome - A. G. Naryshkin; I. V. Galanin; A. L. Gorelik; T. A. Skoromets; A. Y. Egorov; M. N. Abramovskaya; M. Y. Gordeev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
In the article theoretical substantiation of the transtimpanal chemical destruction of vestibular receptors application possibility form dicinal purposes in patients with amnestic syndrome is presented. The results of treatment of 29 patients of male presented. Treatment consisted of acombined application of transtimpanal chemical destruction of vestibular receptors and transcranial direct current stimulation in the projections of the rear of the associative areas of the cerebral cortex. Good positive results were obtained in 25 patients. Before and after the treatment was carried out psychological examination. Tests for the study of different forms of memory and intellect were used. Also electroencephalography testing was carried out. The characteristic dynamics of three-stage restoration of mental functions was noted in all patients. The course of treatment lasted for 4 - 5 weeks. Recovery of cognitive abilities in patients experienced at the end of treatment. A clinical case of showing the results of the treatment is given in the article. The article is illustrated with the results of the electroencephalographic studies in the dynamics. The psycho-physiological positions changes in the spatial synchronization of the cerebral cortex discussed.